Socio-Psychological Drivers of Livelihood Diversification in Lakshadweep - Beevi, Anshida; Wason , Monika; Padaria , R. N.; Kumbhare, N.V.; Varghese, Eldho (Indian Journal of Extension Education, 2015)
Diversification is the incorporation of new activities into the economic portfolio. The rural livelihood diversification  therefore is an integral dimension of development agenda for strengthening rural livelihood and sustaining  livelihood security. The study was conducted among 120 households in Kalpeni and Andrott islands of U.T. of  Lakshadweep to assess the extent of diversification and to analyse the socio-psychological factors promoting  diversification. Respondents were randomly selected and categorized into three livelihood classes based on the share of  agriculture in households' income. Extent of livelihood diversification is studied in terms of number of income  sources of a household and Simpson index of diversification. It is obtained that most of the households were having  diverse livelihood strategy. It has been found that majority of the diversified households have medium diversification  index with average diversification index of 0.32. Determinants of diversification were analyzed using Kruskal-Wallis  test. It was found out that mass media exposure was the most significant factor leading to diversification followed by  social participation, change proneness and achievement motivation.
Keywords: House hold income; livelihood diversification; socio-psychological drivers